2010
DOI: 10.5993/ajhb.34.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Health Care Access in 13 Asian American Communities

Abstract: Objective: To obtain and discuss in-depth information on health care use in Asian Americans (AAs). Methods: Nineteen focus groups were conducted in 174 adults from 13 AA communities in Montgomery County, Maryland. MAX QDA software was used to analyze qualitative data. Results: Financial, physical, communication, and cultural attitudes were 4 major barriers to accessing health care. Underrepresented communities reported unique additional barriers, such as lack of screening opportunities and interpretation servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 26 publications
4
87
0
Order By: Relevance
“…Qualitative research suggests that Asian Americans are less likely to seek care from medical providers due to cultural and linguistic barriers. 11 Our findings are similar to those of Burton et al 5 Those authors also found that Asians had the smallest percentage of employees at high risk in 2009 whereas African Americans had the highest prevalence of four health risks (ie, obesity, blood pressure, safety belt use, and physical activity). The average number of risks among African American employees was significantly higher than that among other ethnic groups after adjusting for age and sex.…”
Section: Discussionsupporting
confidence: 90%
“…Qualitative research suggests that Asian Americans are less likely to seek care from medical providers due to cultural and linguistic barriers. 11 Our findings are similar to those of Burton et al 5 Those authors also found that Asians had the smallest percentage of employees at high risk in 2009 whereas African Americans had the highest prevalence of four health risks (ie, obesity, blood pressure, safety belt use, and physical activity). The average number of risks among African American employees was significantly higher than that among other ethnic groups after adjusting for age and sex.…”
Section: Discussionsupporting
confidence: 90%
“…These women may have had less access to preventative care in their countries of origin. In addition, many cultural and language barriers to healthcare have been identified in this population [14,15]. Attention focused on improving screening, early detection and prevention in these groups will be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Guided by a SDM conceptual model, 3 we identify common experiences of AAPI SGM that fall into three themes: (1) AAPI Heterogeneity, (2) SGM Stigma, and (3) Multiple Minority Group Identities and Sources of Discrimination (Table 1). [4][5][6][7][8]10,12,13,18,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] We created three case studies to illustrate the intersectional issues that can occur in reallife patient-provider encounters among AAPI SGM. We outline potential strategies for clinics and clinicians to improve cultural competency, communication, and SDM (Table 2).…”
Section: An Intersectional Approach To Understanding Sdmmentioning
confidence: 99%
“…However, AAPI SGM may share cultural expectations that support an authoritarian relational structure in patient-provider relationships. 32,48 Dr. Steve may have attributed Michelle's confusion to a lack of English proficiency because of heteronormative assumptions, as well as the implicit racial bias and sentiments that AAPIs are ''perpetual foreigners. '' 30 Sentiments that AAPIs are ''not American enough'' prevail throughout U.S. history and continue to influence social interactions today (Table 1).…”
Section: Case Study 1: Effects Of Stereotypes In Delayed Diagnosismentioning
confidence: 99%
See 1 more Smart Citation